Hot carrier dynamics and carrier-phonon interaction in GaN - Kyhm, K; Taylor, R; Cain, N (2005)
The dynamics of carriers in GaN epilayers is investigated by using femtosecond pump-probe spectroscopy. After the residual chirp on the continuum probe is removed, the normalized difference spectra (NDS) for different probe energies are synchronized, recovering the full time resolution of our laser pulse. Our Monte-Carlo simulation agrees well with the unchirped NDS spectrum, which shows the development of the carrier distribution at early times, where phonon satellites are seen, together with a strong non-thermal electron distribution in the region of the LO-phonon energy arising from the remark-ably strong electron-LO phonon interaction. By employing a new technique which involves the integration of the normalized NDS multiplied by the corresponding energy, a measure of the mean energy of the carriers in non-thermal states is obtained. By comparing the time-dependent energy loss with the theoretical energy loss rate, we estimate the effective temperature of the phonon modes as well as the population of phonons.